Challenges obstructing academic's career experience in community engagement practice: the Nigerian universities experience - Adekalu, Samuel Olutokunbo; Suandi, Turiman; Krauss, Steven Eric; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2018)
Community engagement has been acknowledged as a core function of higher education, along with research and teaching which helps in promoting economic, environmental and socio-cultural development of communities. This article explores the barriers obstructing community engagement activities in Nigerian higher education. Kwara State University, Malete, being an institution with the philosophy of community development is an interesting case in this study. Using in-depth semi-structured qualitative interviews, nine professors of the university were asked to reflect on how they develop academic career through community engagement activities. From data analysis, even though there is documentary evidence on the remarkable successes been achieved and reported with regard to community engagement activities and outreaches by the professors which help to sustain professional identities and, in turn, career development. Four factors were found as a barrier obstructing the professors’ participation in community engagement activities and outreaches. These were, (a) Educational gap between professors and community members, (b) lack of funds to execute community development projects, (c) time constraint due to multiple engagements, and (d) resistant to change by community members. This study discussion and recommendations are timely, as it concludes with a number of crucial issues that future on community engagement in Nigerian higher education need to address.